2012
DOI: 10.1002/esp.3349
|View full text |Cite
|
Sign up to set email alerts
|

Natural and historical variability in fluvial processes, beaver activity, and climate in the Greater Yellowstone Ecosystem

Abstract: Two centuries of human activities in the Greater Yellowstone Ecosystem (GYE) have strongly influenced beaver activity on small streams, raising questions about the suitability of the historical (Euro-American) period for establishing stream reference conditions. We used beaver-pond deposits as proxy records of beaver occupation to compare historical beaver activity to that throughout the Holocene. Forty-nine carbon-14 ( 14 C) ages on beaver-pond deposits from Grand Teton National Park indicate that beaver acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 68 publications
(177 reference statements)
1
42
0
Order By: Relevance
“…Breaching of the abandoned dam can result in at least partial erosion of the pond sediment, although the establishment of rooted aquatic macrophytes and other wetland vegetation commonly limits evacuation of pond sediment (Wohl & Scott ). Beaver pond deposits can remain for thousands of years, as has been shown from late Holocene deposits dated with radiocarbon (Persico & Meyer , , Polvi & Wohl ) or ground‐penetrating radar (Kramer et al. ) methods.…”
Section: Long‐term Carbon Dynamics In Beaver‐affected Patches and Lanmentioning
confidence: 98%
“…Breaching of the abandoned dam can result in at least partial erosion of the pond sediment, although the establishment of rooted aquatic macrophytes and other wetland vegetation commonly limits evacuation of pond sediment (Wohl & Scott ). Beaver pond deposits can remain for thousands of years, as has been shown from late Holocene deposits dated with radiocarbon (Persico & Meyer , , Polvi & Wohl ) or ground‐penetrating radar (Kramer et al. ) methods.…”
Section: Long‐term Carbon Dynamics In Beaver‐affected Patches and Lanmentioning
confidence: 98%
“…Our measurements from Kimages Creek add quantitative support for a recent hypothesis emphasizing a limited impact of beaver dams on landscapes (Persico and Meyer, ; Burchsted and Daniels, ; Levine and Meyer, ). Previous studies of beaver dams have indicated the long‐term impact on channel morphology (Butler, ; Polvi and Wohl, ) included bed aggradation and a decrease in bankfull area, particularly in ponds upstream of beaver dams (Naiman et al ., ; Butler and Malanson, ).…”
Section: Discussionmentioning
confidence: 99%
“…Estimated total carbon storage during periods of active beaver meadows does not imply that all of the extensive meadows were continuously occupied during the Holocene. Although these sites represent optimal beaver habitat, they may all have been simultaneously occupied only during cooler, wetter intervals of the Holocene [ Persico and Meyer , , ]. The estimated carbon storage using 12% TOC and total sediment volume in extensive beaver meadows represents maximum potential carbon storage at the landscape level relative to contemporary, relatively low values.…”
Section: Discussionmentioning
confidence: 99%
“…This valley‐bottom metamorphosis likely has important implications for ecosystem resilience to climate change, drought, and wildfire. Beaver populations and their dam‐induced hydrologic effects have varied during the Holocene in response to climate fluctuations [ Persico and Meyer , , ] and will presumably vary in future. The persistence of at least some beaver, however, and the maintenance of higher riparian water tables probably created Holocene refugia for more mesic communities during drier intervals.…”
Section: Discussionmentioning
confidence: 99%